Observation of Electromyographic Biofeedback Stimulation on Acupoints to Improve Foot Drop in Stroke Patients with Hemiplegia - Lingyan HE; Ling FENG; Zhengyi CHEN (康复学报)
Objective:To evaluate the efficacy of electromyographic biofeedback on acupoints to improve foot drop in stroke patients with hemiplegia.Methods:According to the random number table, forty stroke patients were divided into the control group and the treatment group, each group with 20 cases. Both two groups were treated with same routine rehabilitation training and electromyographic (EMG) biofeedback parameters. EMG biofeedback equipment electrodes were adhesion to Zusanli, Jiexi, Yanglingquan, Shangjuxu acupoints in the treatment group, but those were adhesion to the muscle fiber direction along the electrode surface adhesion in the anterior tibial muscle in the control group. Before treatment and after 8 weeks of treatment, the Fugl-Meyer (FMA) scores of the lower limb function, active range of motion (AROM) of ankle joint and isometric contraction surface EMG integral value (iEMG) of ankle joint maximum flexion of the anterior tibial muscle were used to assess both in two groups respectively.Results:After 8 weeks of treatment, there were statistically significance comparison of the FMA, AROM and iEMG in group (P<0.01) and between two groups (P<0.05).Conclusion:Electromyographic biofeedback stimulation on acupoints can improve stroke patients with foot drop and lower limb motor function effectively.